The Atg8 Conjugation System Is Indispensable for Proper Development of Autophagic Isolation Membranes in Mice - Yu‐shin Sou; Satoshi Waguri; J. Iwata; Takashi Ueno; Tsutomu Fujimura; Taichi Hara; Naoki Sawada; Akane Yamada; Noboru Mizushima; Yasuo Uchiyama; Eiki Kominami; Keiji Tanaka; et al. (2008)
Autophagy is an evolutionarily conserved bulk-protein degradation pathway in which isolation membranes engulf the cytoplasmic constituents, and the resulting autophagosomes transport them to lysosomes. Two ubiquitin-like conjugation systems, termed Atg12 and Atg8 systems, are essential for autophagosomal formation. In addition to the pathophysiological roles of autophagy in mammals, recent mouse genetic studies have shown that the Atg8 system is predominantly under the control of the Atg12 system. To clarify the roles of the Atg8 system in mammalian autophagosome formation, we generated mice deficient in Atg3 gene encoding specific E2 enzyme for Atg8. Atg3-deficient mice were born but died within 1 d after birth. Conjugate formation of mammalian Atg8 homologues was completely defective in the mutant mice. Intriguingly, Atg12-Atg5 conjugation was markedly decreased in Atg3-deficient mice, and its dissociation from isolation membranes was significantly delayed. Furthermore, loss of Atg3 was associated with defective process of autophagosome formation, including the elongation and complete closure of the isolation membranes, resulting in malformation of the autophagosomes. The results indicate the essential role of the Atg8 system in the proper development of autophagic isolation membranes in mice.